Upaya Asatidz dalam Mencegah Ma'ashil Yadain melalui Pembelajaran Akhlaq Kajian Kitab Muroqil Ubudiyah - Ilham Alamsyah; Mujahid Rasyid; Ayi Sobarna (UNISBA Press, 2023)
Abstract. This essay discusses the phenomenon of ma’ashil yadain they are theft and ghasab at Islamic Boarding School, Bandung. This study aims to reveal the causes of the occurrence of acts of theft and ghasab and efforts to overcome them by the teachersthrough a study of the Muroqil Ubudiyah book how to implement it and what solutions can be offered to overcome the theft and the culture of the ghasab. This study uses a descriptive qualitative approach, because researcher want to describe and illustrate how acts of theft and ghasab occur at the Islamic Boarding School. Data collection techniques in this study used direct observation/observation, interviews, and documentation of the head of the boarding school, the teachers administrators and students. Data analysis uses three stages, the first is data reduction, the second is data presentation, and the third is drawing conclusions. The results showed: 1) The theft that occurred at the Islamic Boarding School was caused by several factors including economic factors, urgent circumstances and the carelessness of the owner of the goods while ghasab was caused by 3 factors, namely individual factors: weak awareness of students not to commit ghasab , an innate tradition from the previous environment and likes to belittle the items in the ghasab. Environmental factors: the absence of role models, patterns of interaction that are too close to be abused, and factors of the moral education system: the quality of educators is not maintained, the moral development is not optimal. 2). Efforts to implement prevention through the study of the book of muroqil ubudiyah at Pondok Pesantren are not going well. This is shown by the students who often arrive late for recitation, are not disciplined when reciting the recitation and lack of support from other the teachers 3). Solutions that can be offered as an effort to reduce theft and ghasab in Islamic boarding schools are changing perceptions of ghasab, setting an example not to commit theft and ghasab, making regulations about stealing and ghasab and improving the quality of moral education. For now, efforts have been made by Islamic Boarding School to tackle cases of theft and ghasab culture, namely changing perceptions about stealing and ghasab, doing punishment, and improving the quality of moral education. Abstrak. Skripsi ini membahas fenomena ma’ashil yadain yaitu pencurian dan ghasab di Pondok Pesantren. Penelitian ini bertujuan untuk mengungkap sebab terjadinya tindakan pencurian dan ghasab serta upaya penanggulangannya yang dilakukan asatidz melalui kajian kitab muroqil ubudiyah bagaimana pelaksanaannya serta solusi apa yang bisa ditawarkan guna menanggulangi pencurian dan budaya ghasab tersebut. Penelitian ini menggunakan pendekatan kualitatif deskriptif, sebab peneliti ingin mendeskripsikan dan menggambarkan bagaimana terjadinya tindakan pencurian dan ghasab di Pondok Pesantren. Teknik pengumpulan data dalam penelitian ini menggunakan pengamatan langsung/observasi, wawancara, dan dokumentasi terhadap pimpinan pesantren, asatidz, pengurus dan santri. Analisis data menggunakan tiga tahapan yang pertama reduksi data kedua penyajian data dan yang ketiga penarikan kesimpulan. Hasil penelitian menunjukan: 1) Pencurian yang terjadi di Pondok Pesantren disebabkan oleh beberapa faktor diantaranya adalah faktor ekonomi, faktor keadaan yang mendesak dan faktor kecerobohan si pemilik barang sedangkan ghasab disebabkan oleh 3 faktor yaitu faktor individu: lemahnya kesadaran santri untuk tidak berbuat ghasab, tradisi bawaan dari lingkungan sebelumnya dan suka meremehkan barang yang di ghasab. Faktor lingkungan: tidak adanya sosok teladan, pola interaksi yang terlalu dekat yang disalahgunakan, serta faktor sistem pendidikan akhlak: kualitas pendidik yang kurang terjaga, kurang maksimalnya pembinaan akhlak yang dilakukan. 2). Upaya pelaksaan pencegahan melalui kajian kitab muroqil ubudiyah di Pondok Pesantren, berjalan kurang baik. Hal ini ditunjukkan dengan santri yang sering datang terlambat dalam pengajian, tidak disiplin ketika mengaji dan kurangnya dukungan dari asatidz lain. 3). Solusi yang dapat ditawarkan sebagai upaya mengurangi pencurian dan ghasab di pondok pesantren yaitu mengubah persepsi tentang ghasab, memberi teladan untuk tidak melakukan pencurian dan ghasab, membuat peraturan tentang mencuri dan ghasab serta meningkatkan mutu pendidikan akhlak. Untuk saat ini upaya yang sudah dilakukan Pondok Pesantren untuk menanggulangi kasus pencurian dan budaya ghasab yaitu mengubah persepsi tentang mencuri dan ghasab, melakukan ta’zir, dan meningkatkan mutu pendidikan akhlak.